Securing basic well-being for all: A full characterization - Reiko Gotoh; Naoki Yoshihara (University of Massachusetts, Department of Economics, 2017)
The purpose of this paper is to examine the possibility of a social choice rule to implement a social policy for ìsecuring basic well-being for all.î The paper introduces a new scheme of social choice, called a social relation function (SRF), which associates a reáexive and transitive binary relation over a set of social policies to each proÖle of individual well-being appraisals and each proÖle of group evaluations. As part of the domains of SRFs, the available class of group evaluations is constrained by three conditions. Furthermore, the non-negative response (NR) and the weak Pareto condition (WP) are introduced. NR demands giving priority to group evaluation, while treating the groups as formally equal relative to each other. WP requires treating impartially the well-being appraisals of all individuals. In conclusion, this paper shows that under some reasonable assumptions, there exists an SRF that satisÖes NR and WP.
Keywords: D63; 330; basic well-being; individual well-being appraisals; social relation functions